The Influence of Principal Leadership, Achievement Motivation, and Information Technology Proficiency on the Professional Competence of Vocational High School Teachers - Himawan, Ariza Fadly; Soedjono, Soedjono; Prayito, Muhammad (SAINTIS Publishing, 2025)
This study examines the impact of principal leadership, achievement motivation, and information technology mastery on the professional competence of vocational high school teachers in Rembang Regency. Professional competence is essential for improving learning quality, particularly in implementing the Independent Curriculum, Using a quantitative approach with an ex post facto research design, this study involved 150 vocational high school teachers selected through proportional random sampling. Data were analyzed using simple and multiple regression analysis. The findings reveal that principal leadership significantly influences professional competence, contributing 54.6%. Achievement motivation also has a significant impact, with an effect size of 59.2%, while information technology mastery contributes 55.1%. Simultaneously, the three variables account for 76.2% of the variance in professional competence, indicating their crucial role in enhancing teacher effectiveness. This study suggests that teachers should enhance their professional competence through continuous training and self-development. Additionally, school principals should optimize their leadership by providing guidance and support, particularly in technology integration and fostering achievement motivation.